Prevention of disaster triggered by crowd surge: comparative insights in selected countries and Indonesia - Fajar, Mohamad (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Introduction: Hazards, whether caused by natural or human activities, can potentially lead to disaster. In 2015, the United Nations (UN) at its conference in Sendai, Japan established a framework related to disaster risk reduction to be guided until 2030. However, disaster management related to human-induced hazards has received less attention. The Covid-19 pandemic that has been overcome has made restrictions on human movement begin to loosen. With the increase in travel between regions, countries, and continents, people began to form crowds at events related to religion, entertainment, sports, and other activities. A poorly managed crowd develops into an uncontrolled crowd or riot, and disaster ensues. This paper aims to develop alternative prevention efforts so that similar disasters do not occur in the future. Methods: The method of this paper is a literature review and systematic content analysis of previous scientific articles and research. First, the paper describes disasters at planned events such as music concerts in Texas, United States, and less planned ones such as the Halloween festival in Seoul, South Korea. Then the countermeasures of the two events were compared with the incident in Malang, Indonesia. Finding: The result is that strong cooperation between related parties is needed in organizing events to maintain community safety. The use of technology and tightening regulations can be factors supporting the prevention of this disaster. Increasing the capacity of communities to deal with similar disaster risks is still not widely discussed, so further research is needed. Conclusion: Islamic science is a comprehensive paradigm, similar to Western science, that can serve as a framework for scientists from various fields of knowledge. The Islamic paradigm attempts to critique the concept of universality, which has been one of the values embraced by the Western scientific paradigm. This concept has been one of the reasons why scientific revolutions have occurred slowly.